INFORMATION SUPPORT OF NON-FINANCIAL REPORTING IN A PANDEMIC - MOKRYNSKA, ZORIANA; BOROVYK, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Dissemination of information on the principles of sustainable development implemented in the activities of enterprises and the results of non-financial reporting is usually through the web pages of enterprises. However, this is not the only platform for disseminating such information. Therefore, this article describes the main international platforms that can be used by enterprises. The dynamics of the number of non-financial reports in some European countries and Ukraine is analyzed. Trends and dynamics of the publication of certified non-financial reports in the world and Ukraine are determined. The article summarizes information on major competitions and awards for sustainable development cases and the best non-financial reports. In particular, the results of the selection of the best reports on sustainable development of the CR Reporting Awards 2021 are presented. The article presents the stages of this award, the criteria for selecting non-financial reports and the main nominations. The impact of COVID-19 on non-financial reporting of leading domestic enterprises is analyzed. It has been established that practical social cases related to the pandemic should be identified in the non-financial reporting of enterprises in the following areas: response to COVID-19, support during the pandemic, recovery and sustainability. Information on the results of the impact of COVID-19 on the indicators reflected in the non-financial statements is described. Our paper identifies shifts in the non-financial reporting of enterprises that, due to the pandemic impact, are more focused on social issues such as employee welfare, social welfare, occupational health and safety, and integration and equality. The need to provide reliable information presented in non-financial reporting in a pandemic is objectively justified by the need to increase the demand for social information. During various unforeseen crises, the information interests of stakeholders change. Therefore, to ensure sustainable development, the company needs to provide relevant social information reflected in non-financial statements that will maintain the trust of key stakeholders.
Keywords: non-financial reporting; sustainable development reporting; sustainable development; pandemic; audit